The ontology of information and its metamorphosis in the process of collecting evidence in criminal procedures (Academic Journal of Internal Affairs, 2015)
The author provides a theoretical overview of the process of how information is being processed in criminal investigations.
Keywords: criminal investigations; information; processing process